2011
DOI: 10.1111/j.1742-4658.2011.08146.x
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of an ascomycete fungal laccase from Thielavia arenaria – common structural features of asco‐laccases

Abstract: Laccases are copper‐containing enzymes used in various applications, such as textile bleaching. Several crystal structures of laccases from fungi and bacteria are available, but ascomycete types of fungal laccases (asco‐laccases) have been rather unexplored, and to date only the crystal structure of Melanocarpus albomyces laccase (MaL) has been published. We have now solved the crystal structure of another asco‐laccase, from Thielavia arenaria (TaLcc1), at 2.5 Å resolution. The loops near the T1 copper, formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 64 publications
(73 reference statements)
1
54
0
6
Order By: Relevance
“…Above 35°C, the currents decrease and signal distortion occurs due to protein desorption and/or unfolding. The E°' values for McoG wt and variants are similar to those reported for the T1 center of low potential laccases immobilized within an electrochemically inert polymer coating a gold electrode surface [35] and to those of other asco-laccases [36].…”
Section: Electrochemical Propertiessupporting
confidence: 79%
See 1 more Smart Citation
“…Above 35°C, the currents decrease and signal distortion occurs due to protein desorption and/or unfolding. The E°' values for McoG wt and variants are similar to those reported for the T1 center of low potential laccases immobilized within an electrochemically inert polymer coating a gold electrode surface [35] and to those of other asco-laccases [36].…”
Section: Electrochemical Propertiessupporting
confidence: 79%
“…The crystal structure obtained from crystal form II consists of 549 amino acid residues (the first 21 amino acid residues are not visible), four copper ions, fourteen glucosides, one peroxide molecule and 599 solvent molecules. The two models are very similar and their overall structure is similar to that of other laccases, especially to those from the ascomycetes Melanocarpus albomyces (MaL) [36] and Thielavia arenaria (TaL) ( Figure 4A) [42]. The least square superposition of the Cα atoms of the McoG structure (crystal form I) with those of MaL and TaL gave an rmsd of 1.41 and 1.48 Å, respectively.…”
Section: Structural Propertiesmentioning
confidence: 70%
“…The kinetic data of TaLcc1 thus should fit in between those of the two enzymes. However, data on kinetic parameters of this enzyme (38) showed this not to be the case, suggesting that the redox potential difference between the T1 copper and the substrate may not be the only factor that contributes to substrate oxidation. It has also been reported that a variant of the Pleurotus ostreatus laccase (1H6C) which showed a higher redox potential (by ϩ0.12 V) relative to the wild-type enzyme exhibited catalytic efficiencies similar to those of the wild type on several substrates (39).…”
Section: Discussionmentioning
confidence: 95%
“…Some extremophilic fungi like Penicillium pinophilum isolated from Himalayan region was demonstrated to produce laccase at low temperatures [104]. However the mechanism of action of laccases under extreme conditions is less explored, with crystal structure of only a few laccases being fully known including those from ascomycetes Melanocarpus albomyces (MaL) and Thielavia arenaria (TaLcc1) which differ from other laccases by the presence of a conserved 'C-terminal plug' probably in proton transfer processes [105]. In spite of their tremendous potential in bioremediation, the utility of laccases is restricted by their low shelf life.…”
Section: Laccasementioning
confidence: 99%